Answer:
11
Step-by-step explanation:
6 + 3 = 9
8 + 3 = 11
Answer:
f(g(x)) = 2(x^2 + 2x)^2
f(g(x)) = 2x^4 + 8x^3 + 8x^2
Step-by-step explanation:
Given;
f(x) = 2x^2
g(x) = x^2 + 2x
To derive the expression for f(g(x)), we will substitute x in f(x) with g(x).
f(g(x)) = 2(g(x))^2
f(g(x)) = 2(x^2 + 2x)^2
Expanding the equation;
f(g(x)) = 2(x^2 + 2x)(x^2 + 2x)
f(g(x)) = 2(x^4 + 2x^3 + 2x^3 + 4x^2)
f(g(x)) = 2(x^4 + 4x^3 + 4x^2)
f(g(x)) = 2x^4 + 8x^3 + 8x^2
Hope this helps...
Answer:
<h2>4(5x + 6)</h2>
Step-by-step explanation:
![5(6x+4)-2(5x-2)\qquad\text{use distributive property}\ a(b+c)=ab+ac\\\\=(5)(6x)+(5)(4)+(-2)(5x)+(-2)(-2)\\\\=30x+20-10x+4\qquad\text{combine like terms}\\\\=(30x-10x)+(20+4)\\\\=20x+24](https://tex.z-dn.net/?f=5%286x%2B4%29-2%285x-2%29%5Cqquad%5Ctext%7Buse%20distributive%20property%7D%5C%20a%28b%2Bc%29%3Dab%2Bac%5C%5C%5C%5C%3D%285%29%286x%29%2B%285%29%284%29%2B%28-2%29%285x%29%2B%28-2%29%28-2%29%5C%5C%5C%5C%3D30x%2B20-10x%2B4%5Cqquad%5Ctext%7Bcombine%20like%20terms%7D%5C%5C%5C%5C%3D%2830x-10x%29%2B%2820%2B4%29%5C%5C%5C%5C%3D20x%2B24)
![20x=4\cdot5x\\\\24=4\cdot6\\\\20x+24=4(5x+6)](https://tex.z-dn.net/?f=20x%3D4%5Ccdot5x%5C%5C%5C%5C24%3D4%5Ccdot6%5C%5C%5C%5C20x%2B24%3D4%285x%2B6%29)